Highly sensitive single-step PCR protocol for diagnosis and monitoring of human cytomegalovirus infection in renal transplant recipients. - Caballero, O L (1997)
A multiplex, single-step PCR protocol for the detection of human cytomegalovirus (HCMV) DNA is described. The protocol amplifies regions of the viral LA and IE genes and employs elevated temperatures for both reagent mixing and primer annealing together with product detection by silver staining on polyacrylamide gels. This assay detects one to five HCMV genomes in clinical samples containing up to 100 ng of human DNA, a level of sensitivity equivalent to that of more complex assays involving either nested PCR or postamplification hybridization. As well as being of importance in clinical situations where high-sensitivity qualitative diagnosis is required, this assay is also applicable to the monitoring of HCMV infection in renal transplant recipients. Due to its multiplex format the assay provides quantitative information, in that samples from which a single target is amplified contain on average sevenfold fewer viral genomes per 10(6) leukocytes than those from which both targets are amplified. When weekly blood leukocyte DNA preparations from renal transplant patients were assayed, findings of three consecutive tests in which both HCMV targets were amplified were highly indicative of patients who had developed very high loads of HCMV (100% sensitivity, 88% specificity). We thus show that the same simple PCR assay which permits highly sensitive HCMV diagnosis can also be used for the efficient identification of transplant recipients at risk of clinically significant infection.